The Role of Investor Behavior in Forming Abnormal Return - An Economic Perspective - Ariskha, Nisma; Amiruddin, Amiruddin; Alam, Syamsu (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to conduct a comprehensive analysis of macroeconomic factors influencing abnormal returns and the role of investor behavior in shaping them. Utilizing a systematic literature review, the study is based on the identification of 39 Scopus-indexed articles published between 2014 and 2024, ranging from Quartile Q1 to Q4. The review explores prior research on abnormal returns to identify key findings, macroeconomic factors impacting abnormal returns, and the role of investor behavior in their formation. Using the Research Plan Systematic Literature Review menu in the Watase application, the term "Abnormal Return" was used as the keyword to locate relevant articles. The findings categorize the literature into two main groups: macroeconomic factors affecting abnormal returns and the role of investor behavior in shaping them. Macroeconomic factors such as economic growth, inflation, and general economic conditions significantly influence abnormal returns. Favorable economic conditions enhance company performance, thereby impacting abnormal returns. Furthermore, investor behavior plays a pivotal role, with overreaction to market information often causing abnormal returns, while underreaction can influence long-term return patterns. Investor strategies, including momentum and contrarian trading, are influenced by stock network effects. Understanding these behavioral dynamics is essential to analyzing stock market patterns and their implications for abnormal returns.